AKTIVITAS ANTIOKSIDAN DAN KOMPONEN BIOAKTIF SEMANGGI AIR (MARSILEA CRENATA) - Nurjanah Nurjanah; Aulia Azka; Asadatun Abdullah (UII, 2012)
Water clover (Marsilea crenata) is one type of aquatic plants. Plants that fall into these ferns are found in the rice field, ponds, lakes, swamps and rivers. This plant has a very distinctive morphology of its leaves resemble an umbrella shape that is composed of four petals facing child leaves. In the area of young clover Java is widely used as food. Utilization of clover water not only as food, water clover leaves and stems can also be used as drug . A research about peculiar properties of water clover for human health is very important to do, like antioxidant activity assay and qualitative bioactive compounds assay. The objectives of this research were to determine content, chemical compounds (water, lipid, protein, ash and crude fiber), antioxidant activity and bioactive compounds of water clover. Methods that used in this research were proximate analysis, quantitative antioxidant activity assay using DPPH method, and phytochemical method. Water clover planted first in Laboratorim Characteristics of Raw Water Results, Aquatic Product Technology, FPIK, IPB. Crude extracts from water clover have antioxidant activity that measured as IC50 value. The IC50 value from chloroform extract, ethyl acetate extract, and methanol extract of water clover were 1285,39 ppm; 915,03 ppm dan 634,73 ppm, respectively. The crude extracts of water clover contained 6 bioactive compounds, i.e alkaloid, steroid/triterpenoid, flavonoid, carbohydrate, reducing sugar and free amino acid. These compounds suspected have positive physiology functions for human health, so that water clover can be used for raw material of nutraceutical. Keywords: antioxidant activity, bioactive compound, water clover (Marsilea crenata)